A study of spatial spillover effects of rural human capital on agroecological wellbeing performance: based on empirical data analysis at the provincial in China - Li, Xiaoyuan; Jin, Yule (Frontiers in Sustainable Food Systems, 2025)
IntroductionAgroecological wellbeing performance (AWP) plays a crucial role in fostering sustainable agricultural development and improving overall human welfare. The enhancement of rural human capital is a key factor in bolstering AWP, offering substantial support for its improvement.MethodsThis study utilizes data from 30 provincial regions in China over the period from 2011 to 2022 to assess AWP using the super-efficient SBM model. The spatial Durbin model is employed to analyze the spatial spillover effects of rural human capital on AWP and to explore the underlying mechanisms of its influence.Results and discussionThe findings indicate that improvements in rural human capital have a significant positive impact on AWP, with notable spatial spillover effects. Heterogeneity analysis show that rural human capital significantly enhances AWP in regions with steep topography. In contrast, in Main Grain-Producing Areas (MGPAs), the contribution of rural human capital to AWP is more localized, with limited cross-regional spillover effects. Mechanism analysis further suggests that the development of digital inclusive finance effectively supports high human capital groups in enhancing AWP, while resource mismatches act as a barrier to the full potential of rural human capital in improving AWP. These insights provide valuable guidance for advancing AWP across regions.